Shexiang Baoxin Pill, Derived From the Traditional Chinese Medicine, Provides Protective Roles Against Cardiovascular Diseases - Lu, Li; Sun, Xiaodong; Chen, Chen; Qin, Yating; Guo, Xiaomei (Frontiers in Pharmacology, 2018)
Shexiang Baoxin Pill (SBP), derived from the traditional Chinese medicine, has been broadly applied for the treatment of cardiovascular diseases including coronary heart disease, heart failure, and hypertension in East Asia for decades. Emerging pharmacological studies have revealed that SBP displays pleiotropic roles in protecting the cardiovascular system, as seen by the promotion of angiogenesis, amelioration of inflammation, improvement of endothelium dysfunction, mitigation of dyslipidemia, repression of vascular smooth muscle cell proliferation, and migration and restraint of cardiac remodeling. In terms of clinical practice, the clinical trials and meta-analyses have proved the efficacy and safety of SBP. In this review, we, for the first time, systematically summarize the cardioprotective effects and underlying mechanisms of SBP and provide novel insights into future research directions of SBP based on the experimental and clinical perspectives.